The Effects of Sexual Violence Victimization on Perceived Peer Norms and Social Barriers to Bystander Intervention Among High School Students - Mulla, Mazheruddin M. (Journal of interpersonal violence, 2023)
The experience of sexual victimization may lead to increased threat-biased information processing, including increased perceptions of peer attitudes that condone sexual violence. The perception that peers generally condone sexual violence may in turn inhibit survivors of sexual violence from intervening to address risk for harm among their peers. To assess this possibility, the present study examined the direct and indirect association between sexual victimization by a romantic partner, perceived peer rape myth acceptance (RMA), perceived social barriers to bystander intervention, and bystander behaviors over 2-month follow-up in a sample of 843 high school students. Multiple regression path analyses revealed a sequence of positive associations between sexual victimization, perceived peer RMA, and perceived social barriers to bystander intervention, respectively. These direct associations to be significant among girls, but not boys, and revealed an additional negative direct association between perceived social barriers to bystander intervention and bystander behavior over 2-month follow-up among girls. Furthermore, sexual victimization was indirectly associated with decreased bystander behaviors among girls through perceived peer RMA and perceived social barriers to bystander intervention, respectively. Taken together, the current findings highlight the importance of addressing misperceptions of peer norms among survivors of sexual violence in bystander intervention programs.